Let the centers of four circles with the radius $R=a$ be on 4 vertexs a square with edge size $a$. How calculate the shaded area in this picture?

enter image description here


3 Answers 3


Let $(APD)$ be the area of the figure $APD$.

And let $x,y,z$ be $(KEPM),(PAD),(MPD)$ respectively.

First, we have $$(\text{square}\ ABCD)=a^2=x+4y+4z.\tag1$$

Second, we have $$(\text{sector}\ BDA)=\frac{\pi a^2}{4}=x+2y+3z.\tag2$$

Third, note that $KA=KD=a$ and that $(\triangle KAD)=\frac{\sqrt 3}{4}a^2$ since $\triangle KAD$ is a equilateral triangle.

So, since we have $$\begin{align}(K(E)AD(M))&=(\text{sector}\ AKD)+(\text{sector}\ DKA)-(\triangle KAD)\\&=\frac{\pi}{6}a^2+\frac{\pi}{6}a^2-\frac{\sqrt 3}{4}a^2\\&=\frac{\pi}{3}a^2-\frac{\sqrt 3}{4}a^2,\end{align}$$ we have $$\frac{\pi}{3}a^2-\frac{\sqrt 3}{4}a^2=x+y+2z.\tag3$$

Solving $(1),(2),(3)$ gives us $$(KEPM)=x=\left(1+\frac{\pi}{3}-\sqrt 3\right)a^2.$$


Here is a geometric solution.

Let's find the angle $EDK$. Since $KA=KD=a=AD$ hence the triangle $AKD$ is equiliteral and the angle $KDA$ is $\pi/3$. Therefore angle $KDC$ is $\pi/6$. In the same way the angle $EDA$ is also $\pi/6$ and we get that the angle $EDK$ is $\pi/6$.

Now the shaded area $$(EPMK) = ({\rm square\,} EPMK) + 4\times ({\rm segment\,}EKE).$$

The edge of the square $EPMK$ (from the triangle $EDK$) is $$EK=2a\sin\frac{\pi}{12}=a\frac{\sqrt{3}-1}{\sqrt{2}},$$ hence the area $$({\rm square\,} EPMK) =(2-\sqrt{3})a^2.$$

And the area $$({\rm segment\,}EKE) = \frac{1}{2}\left(\frac{\pi}{6}-\sin\frac{\pi}{6}\right)a^2=\frac{1}{4}\left(\frac{\pi}{3}-1 \right)a^2.$$

So $$(EPMK) = (2-\sqrt{3})a^2 + \left(\frac{\pi}{3}-1 \right)a^2=\left(\frac{\pi}{3}+1-\sqrt{3}\right)a^2.$$


Well this one is very easy to solve. We put a coordinate system directly in the middle of your square. The upper arc from the top left to bottom right is a quater circle and can be considered the graph of a function $g$. Now, since it is on a circle that must have its middle point at $(-a/2,-a/2)$, $g$ satisfies $$ (g(x)+a/2)^2 + (x + a/2)^2 = a^2,$$ because $a$ is its radius. Now we solve this equation for $g(x)$, keeping in mind, that it is the upper half of the circe and get $$ g(x) = \sqrt{a^2 - (x+a/2)^2} - a/2. $$ Due to the symmetry along the line $x=y$, it must be $g(g(0)) = 0$. Due to further symmetries, we get the area as $$ A = 4\int_0^{g(0)} g(x)\,dx. $$ We can easily see, by standard integration techniques, that $$ G(x) = \frac{1}{8} \left(4 a^2 \tan ^{-1}\left(\frac{a+2 x}{\sqrt{(a-2 x) (3 a+2 x)}}\right)-4 a x+(a+2 x) \sqrt{(a-2 x) (3 a+2 x)}\right) $$ is an antiderivative. Now we use the fundamental theorem of calculus and finally get $$ A = 4(G(g(0)) - G(0)) = 4 \frac1{12} a^2 (3 - 3\sqrt 3 + \pi) = a^2(1 - \sqrt 3 + \pi/3).$$

  • $\begingroup$ Sorry for sounding so cocky. I wrote this for someone who asked the same question, but was very rude in formulating it. It was closed before I could post the answer but I didn't want it to go to waste. :) $\endgroup$ Nov 8, 2017 at 13:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.